A prior placenta accreta is an independent risk factor for post-partum hemorrhage in subsequent gestations. (April 2015) - Vinograd, Adi; Wainstock, Tamar; Mazor, Moshe; Mastrolia, Salvatore Andrea; Beer-Weisel, Ruthy; Klaitman, Vered; Dukler, Doron; Hamou, Batel; Benshalom-Tirosh, Neta; Vinograd, Ofir; Erez, Offer
Abstract: Objective: The rate of placenta accreta, a life threatening condition, is constantly increasing, mainly due to the rise in the rates of cesarean sections. This study is aimed to determine the effect of a history of placenta accreta on subsequent pregnancies. Study design: A population based retrospective cohort study was designed, including all women who delivered at our medical center during the study period. The study population was divided into two groups including pregnancies with: (1) a history of placenta accreta ( n = 514); and (2) control group without placenta accreta ( n = 239, 126). Results: (1) A history of placenta accreta is an independent risk factor for postpartum hemorrhage (adjusted OR 4.1, 95% CI 1.5–11.5) as were placenta accreta (adjusted OR 22.0, 95% CI 14.0–36.0) and placenta previa (adjusted OR 7.6, 95% CI 4.4–13.2) in the current pregnancy, and a prior cesarean section (adjusted OR 1.7, 95% CI 1.3–2.2); (2) in addition, placenta accreta in a previous pregnancy is associated with a reduced rate of mild preeclampsia in future pregnancies (1.8% vs. 3.4%, RR 0.51, 95% CI 0.26–0.98); (3) however, in spite of the higher rate of neonatal deaths in the study group, a history of placenta accreta was not an independent risk factor for total perinatal mortality (adjusted OR 1.0, 95% CI 0.5–1.9) after adjusting for confounders. Conclusion: A history of placenta accreta is an independent risk factor for postpartum hemorrhage. This should be taken into account in order to ensure a safety pregnancy and delivery of these patients.